2019
DOI: 10.1002/lno.11199
|View full text |Cite
|
Sign up to set email alerts
|

Optical characterization of marine phytoplankton assemblages within surface waters of the western Arctic Ocean

Abstract: An extensive data set of measurements within the Chukchi and Beaufort Seas is used to characterize the optical properties of seawater associated with different phytoplankton communities. Hierarchical cluster analysis of diagnostic pigment concentrations partitioned stations into four distinct surface phytoplankton communities based on taxonomic composition and average cell size. Concurrent optical measurements of spectral absorption and backscattering coefficients and remote‐sensing reflectance were used to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 88 publications
1
10
0
Order By: Relevance
“…Inverse correlations were observed between fucoxanthin and a phy ( 673)" (r = 0.46; p < 0.001), likely driven by dominance of large taxa with increasing seascape class (Figure 5); fucoxanthin is a diagnostic pigment of large phytoplankton groups such as diatoms. Several other studies have found a consistent effects of diatom concentrations on a phy spectra at this wavelength or in its close vicinity across different ocean regions (Werdell et al, 2014;Lorenzoni et al, 2015;Catlett and Siegel, 2018;Reynolds and Stramski, 2019).…”
Section: Discussion Phytoplankton Pigments and Inherent Optical Properties Of Seascapessupporting
confidence: 68%
“…Inverse correlations were observed between fucoxanthin and a phy ( 673)" (r = 0.46; p < 0.001), likely driven by dominance of large taxa with increasing seascape class (Figure 5); fucoxanthin is a diagnostic pigment of large phytoplankton groups such as diatoms. Several other studies have found a consistent effects of diatom concentrations on a phy spectra at this wavelength or in its close vicinity across different ocean regions (Werdell et al, 2014;Lorenzoni et al, 2015;Catlett and Siegel, 2018;Reynolds and Stramski, 2019).…”
Section: Discussion Phytoplankton Pigments and Inherent Optical Properties Of Seascapessupporting
confidence: 68%
“…For upcoming hyperspectral remote sensing platforms, maintaining all the spectral signatures as unbiased as possible is key for developing algorithms that can exploit the small nm‐level variations in the spectra (Giardino et al 2014), potentially allowing even the determination of phytoplankton community composition (Xi et al 2015; Zheng and DiGiacomo 2018; Reynolds and Stramski 2019). In this work, we describe a new approach of sequential methanol extraction and NaOCl bleaching that retrieves the NAP and algal fractions which, after appropriate fitting procedures, avoids most of the biases introduced by these methods separately.…”
Section: Symbol (Abbreviation) Units Definition Sourcementioning
confidence: 99%
“…Clusters that are considered more similar (i.e., shortest distance) are then used to generate larger clusters. Previous work has demonstrated the utility of HCA on water quality classifications and aquatic properties (Brezonik et al, 2005;Kamble and Vijay, 2011;Reynolds and Stramski, 2019).…”
Section: Hierarchical Cluster Analysis and Principal Component Analysesmentioning
confidence: 99%